Professor M.O.A. Abdul (1926-1997): an Indispensable Personality in the Field of Arabic and Islamic Studies in Nigeria - Olarewaju, Yusuph Badmas; Gambari, Yusuph Dauda (Islam Transformatif : Journal of Islamic Studies, 2023)
AbstractThe twin fields of Arabic and Islamic Studies play a critical role in advancing the understanding and practice of Islam among Muslims. Informal learning of these subjects had taken place in Nigeria for centuries before their incorporation into the country's curriculum. Despite the daunting challenges, some indigenous individuals dedicated themselves to bringing these courses to a prestigious level, pioneering their study, and teaching them across schools in the country. However, these quintessential personalities still need due recognition through adequate dissemination of information about their lives and works. One of these pioneers was Professor Musa Oladipupo Ajilogba Abdul, Nigeria's first indigenous Professor of Islamic Studies, who taught and authored many works to simplify the teaching and understanding of Islam for Nigerians. The objective of this paper is to evaluate his activities and to shed light on his enduring legacy, mainly through his former students, mentees, and those scholars who pass through his former students. Using a historical method, the research gathered information through interviews and available library materials. The findings revealed that Prof. M.O.A. Abdul was an iconic academic with an everlasting legacy that is difficult to match. His former students are leading Islamic Studies scholars in Nigeria and beyond, exhibiting his teachings and principles. The paper concluded by recommending a revivalist approach to make Prof. M.O.A. Abdul more relevant in learning Islamic Studies in Nigeria by reproducing his works and domesticating his philosophy by his students and grand-students.Â Bidang integrasi antara Studi Islam dan Bahasa Arab memainkan peran penting dalam memajukan pemahaman dan praktik Islam di kalangan umat Islam. Pembelajaran informal terhadap mata pelajaran ini telah berlangsung di Nigeria selama berabad-abad sebelum dimasukkan ke dalam kurikulum negara tersebut. Terlepas dari tantangan yang berat, beberapa masyarakat adat mendedikasikan diri mereka untuk membawa kursus-kursus ini ke tingkat yang bergengsi, merintis studi mereka, dan mengajarkannya di seluruh sekolah di negara ini. Namun, tokoh-tokoh penting ini masih memerlukan pengakuan melalui penyebaran informasi yang memadai tentang kehidupan dan pekerjaan mereka. Salah satu pionirnya adalah Profesor Musa Oladipupo Ajilogba Abdul, Profesor Studi Islam pribumi pertama di Nigeria, yang mengajar dan menulis banyak karya untuk menyederhanakan pengajaran dan pemahaman Islam bagi orang Nigeria. Artikel ini bertujuan mengevaluasi aktivitasnya dan menjelaskan warisan abadinya, terutama melalui mantan muridnya, para mentee, dan para ulama yang melewati mantan muridnya. Dengan menggunakan metode sejarah, penelitian ini mengumpulkan informasi melalui wawancara dan bahan pustaka yang tersedia. Temuan mengungkapkan bahwa Prof. M.O.A. Abdul adalah seorang akademisi ikonik dengan warisan abadi yang sulit ditandingi. Mantan muridnya adalah cendekiawan Studi Islam terkemuka di Nigeria dan sekitarnya, yang menunjukkan ajaran dan prinsipnya. Makalah ini diakhiri dengan merekomendasikan pendekatan revivalis untuk menjadikan Prof. M.O.A. Abdul semakin relevan mempelajari Studi Islam di Nigeria dengan memperbanyak karya-karyanya dan menjinakkan filosofinya oleh para murid dan cucunya.